OPPORTUNITIES AND CHALLENGES OF ARTIFICIAL INTELLIGENCE IN ACCOUNTING: ARE ACCOUNTING STUDENTS READY TO ADOPT AND DEVELOP IT? - Jadiid Ayyasy; Rizky Rafy Mahendra; Ani Fitriani; Richatul Jannah; Ariq Syuja Prakosa (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the readiness of accounting students in adopting and developing AI. This research aims to obtain a comprehensive insight into the knowledge, perceptions, and readiness of accounting students in adopting and developing Artificial Intelligence (AI) in the context of accounting. The results of the study show that the readiness of accounting students to face AI opportunities and challenges is still quite low. The research shows that the higher students' knowledge of AI concepts and applications, and the better their perceptions of AI opportunities and challenges, the higher their readiness to face AI integration will be. The findings of this study are expected to complement the academic literature by providing new insights into the opportunities and challenges faced by accounting students in adopting and developing AI technologies in the accounting context. Methods: This research method uses a quantitative descriptive method with data collected through questionnaires distributed to respondents as an instrument used on the object of research, namely accounting students who are studying in Semarang City, Indonesia. The technique is used in collecting samples using the purposive sampling method. The analysis methods used include a Descriptive Test, Validity Test, Reliability Test, Determination Coefficient, Classical Assumption Test, and Multiple Linear Regression with F Test and T-test. Results: The results of the study show that the readiness of accounting students to face AI opportunities and challenges is still quite low. The research shows that the higher students' knowledge of AI concepts and applications, and the better their perceptions of AI opportunities and challenges, the higher their readiness to face AI integration will be. The findings of this study are expected to complement the academic literature by providing new insights into the opportunities and challenges faced by accounting students in adopting and developing AI technologies in the accounting context. Keywords: Artificial Intelligence, Accounting Students, Accounting Technology.